Foreword: Special Issue: New Zealand Leading Cases - Dorsett, Shaunnagh; McLay, Geoff (Victoria University of Wellington Law Review, 2010)
This article serves as foreword for this issue of the Victoria University of Wellington Law Review presenting the papers presented at the New Zealand Leading Cases Conference held at the Faculty of Law, Victoria University of Wellington in June 2010. The Conference celebrated the New Zealand Lost Cases project, which aimed to identify and collect cases decided by the New Zealand Superior Courts before the official beginning of law reporting in 1883.